Peran Sarekat Islam dalam Penyebaran Politik Sosialisme di Indonesia - Dio Saputra (Jurnal Politikom Indonesiana, 2025)
This study examines the role of the Sarekat Islam (SI) in disseminating socialist politics in Indonesia during the national movement era. The background of this research lies in SI’s transformation from an economic association into a political organization that shaped indigenous social consciousness and ideology toward social justice. This study employs a qualitative method using a historical approach, including heuristic, verification, and historiography stages to systematically trace SI’s development. The analysis applies H.O.S. Tjokroaminoto’s theory of Islamic socialism, which emphasizes the integration of Islamic values and social justice as the foundation for resistance against colonial oppression. The findings reveal that Sarekat Islam played a major role as a pioneer in spreading socialist ideas grounded in religious values through organizational networks, education, and publications. Furthermore, internal dynamics such as the division between White SI and Red SI reflect ideological tensions that enriched national political thought. In conclusion, Sarekat Islam served as a crucial foundation for the emergence of modern political consciousness and the integration of socialism within the Islamic context of Indonesia. Keywords: Islam, National Movement, Politics, Sarekat Islam, Socialism